Scripture in Early Christianity 14th Annual Conference Asia-Pacific Early Christian Studies Society (Sydney, Australia, 25-27.09.2025) - Wysocki, Marcin (Vox Patrum, 2025)
Report from 14th annual conference Asia-Pacific Early Christian Studies Society (APECSS), titled: Scripture in Early Christianity, which took place on 25-27.09.2025 in Sydney, Australia.